(untitled) (Research, Society and Development, 2020)
To innovate in health education or enhance it, it is essential to provoke reflections about active methodologies, considering that they involve learning as a process built by the person who participates in the method, and not simply reproduce knowledge in a mechanical and uncritical way. This is a study with the objective of demonstrating an experience with learning objects developed by nursing students, in order to socialize knowledge about ‘communicable diseases of epidemiological importance’ using digital applications. The construction of the learning objects was made in a curricular component of the fifth semester of a nursing course in a regional university, located in a municipality in the northwest region of the state of Rio Grande do Sul. It was an innovative, motivating and creative experience in discipline and obtained full participation from academics. It is believed that working in the universe of the digital native favors teaching learning and provides elements with power to teach teachers and qualify teaching.